Measuring the performance of national oil companies in creating value Conceptual model - Diab, Malak Othman; Hammoud, Jamil Ali; Farhat, Mohamed Youssef; Atyeh, Mohamad (Edelweiss Applied Science and Technology, 2025)
This research aimed to present a conceptual model that forms the essential basis for collecting value creation indicators by national oil companies, addressing the lack of Arab studies in this area, to the best of the researchers' knowledge. The study employed a descriptive approach and utilized procedural analysis to identify the components of the value creation index used to measure the performance of national oil companies. These components were summarized into a composite index by assigning weights to each sub-indicator. The research concluded that five categories—state context, sectoral organization and governance, national oil company strategy, national oil company governance, and geology—contribute to value creation by national oil companies. Additionally, the study highlights the importance of linking these categories to clear operational, financial, and national-mission indicators. This connection strengthens the model and enhances understanding of how different factors drive value. By doing so, the study provides a practical framework that policymakers and researchers can rely on when evaluating national oil company performance across diverse contexts. It also offers meaningful practical implications by supporting informed decision-making and creating opportunities for future research to test, refine, and expand the proposed model.